Physico-chemical properties and proximate analysis of fresh and dried karonda (Carrisa carandas) - Meti, Renuka; B, Sunita (Journal of Postharvest Technology, 2023)
Karonda (Carrisa carandas) is an important minor edible underexploited fruit crops. This study was designed to explore the physicochemical  properties and proximate values of fresh and dried karonda. Fresh fruits were collected in the month of June and July. Well-matured fruits were  harvested using hand picking and then sorted based on their color and uniformity. Proximate analyses of fresh and dried Karonda were  performed using standard procedures. The results showed that the physical properties like length of fresh and dried karonda were 7.4±0.87 (cm)  and 4.6±0.90(cm), width of the fresh and dried was found 7.3±0.75 (cm). Density of fresh and dried karonda were found 0.63±0.00(g/ml) and  0.65±0.01(g/ml) respectively. The proximate results of fresh karonda were as follows: carbohydrate, (16.72±1.21%); protein (1.68±0.16%); fat  (1.94±0.42%), moisture (87.29±0.73%); ash (1.32±0.05%), fiber (1.46±0.09%) and dried karonda had carbohydrate (61.51±1.21%), protein  (2.07±1.07%), fat (4.47±0.30%), moisture (28±1.41%); ash (2.12±1.07%), fiber (1.92±0.01%), respectively, The study revealed that the fresh  and dried karonda have good potent of nutritional composition. The nutritive composition varies from fresh karonda to dried karonda, which  could be a range of commercialized fruits for dietary supplements, helping the economy of poor people if value-added products are encouraged.
Keywords: Karonda; drying; physical property; proximate analyses